BECOMING A DYNAMICS 365 FINANCE AND SUPPLY CHAIN SOLUTION ARCHITECT implement industry-grade finance and supply chain solutions for successful enterprise resource planning (ERP) - DAWSON, BRENT (PACKT PUBLISHING LIMITED, 2023)
Reap the full potential of D365 Finance and Supply Chain Management with tips, best practices, proven architectural design concepts, and solutions to common challenges Purchase of the print or Kindle book includes a free PDF eBook Key Features Learn to use Microsoft Fasttrack to successfully implement and deploy D365 F&SCM solutions Understand architectural considerations and best practices for D365 Finance and SCM applications Gain expert guidance on data migration, complex integration, security, and licensing Book Description Implementing an ERP project is a daunting task, and it can often get derailed due to several reasons, including but not limited to inefficient planning, inadequate resource scoping, insufficient working knowledge of ERP systems, and more. Becoming a Dynamics 365 Finance and Supply Chain Solution Architect helps you understand the intricacies of ERP project implementation for seamless deployment. This comprehensive guide helps you gain a deep understanding of how to implement and optimize robust business applications that meet the evolving needs of organizations. You'll discover various integration methodologies to integrate different software applications and plan successful data migration seamlessly. By leveraging the author's expertise, you'll explore different challenges that can lead to project failure or cost/time overruns, along with customized solutions to maneuver past those issues for a successful outcome. By the end of the book, you'll be able to identify potential issues that can negatively impact the delivery of the project and make design decisions that will prevent any potential negative impact on the design and functionality of the system at go-live stage. What you will learn Design an architectural solution for Dynamics 365 with the Fasttrack method Discover potential issues that occur while integrating D365 Finance & Supply Chain Management Set up industry-standard yet customized security configurations Scope license requirements and apply license rules during deployment Plan and test for successful data migration and system integration Identify required tools, applications, and methods for ALM Explore different aspects of human change management in D365 F&SCM projects Who this book is for This book is for aspiring Microsoft D365 finance and supply chain solutions architects looking to take up the challenges of integrating different systems, configuring security models, complex data migrations, licensing, and overall system design based on client requirements. Furthermore, this book serves as a valuable guide for experienced solution architects seeking to expand their skill set and enhance their expertise in tackling complex challenges within the field.